The extraction of lignin from empty fruit bunch fiber via microwave-assisted deep-eutectic solvent heating - Muryadi, I. S.; Yaakob, M. N. A.; Rasidi, Roslan (Universiti Malaysia Pahang, 2021)
This work study about the extraction of lignin from Empty Fruit Bunch (EFB). It is a type of lignocellulosic waste produced during the palm oil extraction process. There are three main components of lignocellulosic, which is one of them is lignin. A deep eutectic solvent (DES) with microwave-assisted heating has been used as a process to extract the lignin from EFB and turn it into a value-product. This convenient method was started with the mixing of EFB and DES. After that, the mixture was heated via microwave synthesis reactor at different temperature and time parameters. The extracted lignin yield was dried and ground into a powder form. The highest lignin yield recovered is 30 % by the highest time and temperature. Interestingly, the purity of all lignin yields are above than 80 %. The highest yield of lignin was characterized. According to Fourier-Transform Infrared (FTIR) spectra, there was a significant functional group of phenolic and aliphatic hydroxyl in lignin. Besides, the methoxy group was also configured in lignin spectra. The presence of conjugated alkene also conveyed the characteristic of lignin. The FTIR spectra were intensified with 1H Nuclear Magnetic Resonance (NMR) spectra where there was a chemical shift in lignin and raw EFB which was designated to aliphatic and aromatic protons bonded to a carbon atom. Three regions of decomposition occur in the Thermogravimetric Analysis (TGA) spectra. The initial decompose temperature of lignin was lower compare to raw EFB. Next, second-stage lignin decomposed at 434.14 ℃ with weight loss of 36.21 %. Lastly, for the final stage, lignin decomposes at 552.54 ℃. Moreover, Differential Scanning Calorimetry (DSC) spectra demonstrate that the Tg value of lignin managed to be identified. However, the Tg value of raw EFB cannot be well defined. As for the characterization in residual fractions of EFB, the lowest crystallinity index (CrI) value of raw EFB has proven the presence of lignocellulosic in its structure. The residual fractions that reacted at higher temperatures have an inflated value of CrI as they contain abundant left out cellulose.